2016
DOI: 10.1111/cch.12432
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mothers' active engagement with infants at 6 months and children's adjustment to school life at ages 5.5 and 11 years

Abstract: Among matched pairs, we observed higher risks of poor adjustment to school life at both 5.5 and 11 years among Japanese children who lacked mothers' active engagement at 6 months. For example, the relative risk was 1.46 [95% confidence interval: 1.10, 1.94] for inability to get along with others in a group setting at the age of 5.5 years and 1.29 [1.10, 1.51] for inability to get along with teachers at the age of 11 years. Our findings corroborate previous findings, which emphasize the importance of providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The latent variable of positive relationships with friends and school teachers was positively and directly associated with children’s feelings towards attending school. Previous studies emphasized the importance of positive relationships with friends and teachers for overcoming school nonattendance [ 11 24 ]. This study found that these relationships were important for positive perceptions of attending school for elementary school students in the 5th year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latent variable of positive relationships with friends and school teachers was positively and directly associated with children’s feelings towards attending school. Previous studies emphasized the importance of positive relationships with friends and teachers for overcoming school nonattendance [ 11 24 ]. This study found that these relationships were important for positive perceptions of attending school for elementary school students in the 5th year.…”
Section: Discussionmentioning
confidence: 99%
“…Variables and the potential relationships among variables were identified based on previous studies [ 1 – 16 , 18 24 ] and Japanese national guidelines [ 17 ]. Key areas of interest included relationships with peers, relationships with school teachers, communication, sharing of experiences and emotions, and health conditions or health problems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers can support mental health among elementary school children [14]. Thus, children's access to supportive adults, particularly teachers, is important [15][16][17][18][19][20]. However, school teachers are responsible for a wide range of students in the classroom and may not have the time or knowledge to provide individualized support.…”
Section: Introductionmentioning
confidence: 99%
“…Elementary school children who are not liked by their classmates or who have no or only a few friends are at risk of bullying [8,9] with associated emotional and behavioral needs [10][11][12][13].Teachers can support mental health among elementary school children [14]. Thus, children's access to supportive adults, particularly teachers, is important [15][16][17][18][19][20]. However, school teachers are responsible for a wide range of students in the classroom and may not have the time or knowledge to provide individualized support.…”
mentioning
confidence: 99%